The Threat of Artificial Intelligence to the Accounting and Management Profession: The Vital Role of Higher Education Institutions in Indonesia - Darmanto, Susetyo; Malik, Ahmad; Purnama, Aditya (Untag Business and Accounting Review, 2025)
The rapid development of Artificial Intelligence (AI) has raised global concerns about the automation of white-collar jobs. In Indonesia, this debate is urgent due to the high volume of standard clerical and cognitive jobs that are vulnerable to automation. This study aims to identify and analyse the threat mechanisms of AI to two strategic professions in accounting and management, and to formulate a comprehensive curriculum transformation agenda for higher education institutions. This study uses a literature review approach by reviewing literature from academic databases, industry reports (WEF, McKinsey, PwC, WordBank), and local data (e.g., the World Bank's Indonesia's Online Vacancy Outlook) from 2018 to 2025. The data was analysed using qualitative descriptive method. The results indicate that the threat of AI is shifting from total professional substitution to automation of routine tasks, which risks eliminating entry-level positions. The findings confirm that successful professions are those that transformation from compliance-based to AI-powered strategic advisors. This transformation requires accounting and management curricula to focus on data analytics, AI ethics, and critical thinking, moving away from the focus on basic calculations or procedures.